The Implementation Of Smart Cities Can Effect The Poverty Rate Reduces In The East Barito District - Miar Miar (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This study aims to update our knowledge of learning literature about the factors that influence poverty and its relation to smart city development. The data collection technique uses a secondary data approach with sources from BPS Barito Timur. This research focuses on how the independent variables affect the dependent variable either partially (single) or simultaneously (together) in the context of smart city development using Excel and the Eviews application 12. The results obtained based on this research simultaneously have a relevant or influential impact on economic growth, population, unemployment, and HDI and how these factors relate to innovative city development. In addition, the positive economic growth achieved individually affects poverty. The unemployment rate and the HDI negatively impact the poverty threshold, which can be addressed through intelligent city development initiatives.